Strategi Pemasaran Melalui Media Sosial dalam Meningkatkan Penjualan : Studi Kasus Yowes Mie - Husnah, Dalilatul; Fahrudin, Fahrudin (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
Digitalization is growing rapidly, especially in marketing strategies through social media applications, so that it can increase sales. Yowes Mie business utilizes social media as an effective and efficient means of promotion. The purpose of this study is to determine effective social media marketing strategies in increasing sales of the Yowes Mie business. This study is expected to be a reference in designing a more appropriate marketing strategy for the development of digital technology. Proper use of social media can be an efficient solution to increase sales and expand market reach without having to spend a lot of money. This study uses a qualitative method using field research. Data were collected through in-depth interviews with business owners, employees, and consumers, as well as direct observation of marketing activities on social media such as Instagram and TikTok. Documentation in the form of promotional content, customer comments, and sales reports were also analyzed to support data validity. This approach was chosen to explore in depth the marketing practices carried out and their impact on the business. The results of the study indicate that marketing strategies through social media are effective in increasing sales at the Yowes Mie business. The marketing strategy used by Yowes Mie through social media includes the use of attractive visual content by uploading aesthetic photos and creative videos used to increase consumer appeal, the use of interactive features such as stories and reels. As well as the preparation of a consistent upload schedule, namely the content "Kamies Manies", a challenge giveaway held every Thursday. This strategy is also supported by the selection of platforms that are in accordance with the target market, namely Instagram and TikTok, which are popular among young people. The results of implementing this strategy show a gradual increase in sales.